Biochemical and technological properties of moose (Alces alces) recombinant chymosin - D. V. Balabova; A. P. Rudometov; S. V. Belenkaya; A. N. Belov; A. D. Koval; A. A. Bondar; A. Yu. Bakulina; E. A. Rukhlova; V. V. Elchaninov; D. N. Shcherbakov (Вавиловский журнал генетики и селекции, 2022)
Recombinant chymosins (rСhns) of the cow and the camel are currently considered as standard milk coagulants for cheese-making. The search for a new type of milk-clotting enzymes that may exist in nature and can surpass the existing “cheese-making” standards is an urgent biotechnological task. Within this study, we for the first time constructed an expression vector allowing production of a recombinant analog of moose chymosin in the expression system of Escherichia coli (strain SHuffle express). We built a model of the spatial structure of moose chymosin and compared the topography of positive and negative surface charges with the correspondent structures of cow and camel chymosins. We found that the distribution of charges on the surface of moose chymosin has common features with that of cow and camel chymosins. However, the moose enzyme carries a unique positively charged patch, which is likely to affect its interaction with the substrate. Biochemical and technological properties of the moose rChn were studied. Commercial rСhns of cow and camel were used as comparison enzymes. In some technological parameters, the moose rChn proved to be superior to the reference enzymes. Сompared with the cow and camel rСhns, the moose chymosin specific activity is less dependent on the changes in CaCl2 concentration in the range of 1–5 mM and pH in the range of 6–7, which is an attractive technological property. The total proteolytic activity of the moose rСhn occupies an intermediate position between the rСhns of cow and camel. The combination of biochemical and technological properties of the moose rСhn argues for further study of this enzyme.